George Pickford wedding portrait, 1886 - Pickford, Joel:::::::::
George Pickford (1861-1941) married Ida Studer in 1886. He was 25 and she was 23. They are Rollin's grandparents. George was born in Trempealeau County, Wisconsin in 1861. There his English immigrant parents had obtained free land from the U.S. Government in exchange for settling and developing it. In 1875, the family moved to California. Following brief stints in Oakland and San Simeon, they settled permanently in Fresno in 1881. George had only an eighth grade education and, like all of his siblings and parents, did physical labor from an early age, including cattle wrangling near Cambria as a teenager. Arriving in Fresno at age 20, he lost parts of two fingers working in Maddary's Lumber Mill. He opened his first business, a butcher shop, in the early 1880s. It was a very profitable business that required little capital, since farmers bore all the expense of raising the animals. Thus, with very little savings and an intense work ethic, George launched a very successful career as a self-made entrepreneur. He went on to buy several failing businesses and turn them around. These included a livery stable, a boarding house, and the City Bakery and Cafe. He also served as market master for the farmer's market located in Fresno's courthouse park. In 1908, he was elected to the Fresno City Board of Trustees, the equivalent of today's City Council. Politically, he identified with the California Progressive Movement led by Hiram Walker and was a political ally of Fresno Mayors Chester Rowell and Alva E. Snow. Retiring from the Board of Trustees in 1920, George purchased the Kohler Laundry from the husband of his deceased sister, Lottie Pickford Kohler, and set up his sons, Rollin Sr. (the artist's father) and William, to run the business for the next 20 years. At the Kohler Laundry, later renamed Liberty Laundry, George was known for always being the first one to arrive at work and the last one to leave. The oval frame on this photo is a modern replacement.